Greeting Word in The Buol Language - Nadia Pratiwi Laindjong; Idris Pattekai; Ulinsa; Syamsuddin (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study aims to describe the forms and usage of address terms in the Buol language as used by the community in Kali Subdistrict, Biau District, Buol Regency. The Buol language possesses a system of address that reflects social structure, kinship relations, and local cultural values. Using a qualitative descriptive approach, data were collected through observation, interviews, recording, and note-taking techniques. The findings reveal seven forms of address terms: (1) pronominal address, (2) personal names, (3) kinship terms, (4) social status, (5) community figures, (6) physical-based nicknames, and (7) habitual-based nicknames. The use of address terms depends on factors such as age, social position, kinship ties, and the context of formal or informal situations. This research highlights the importance of documenting and preserving the Buol language and encourages younger generations to safeguard this cultural heritage.